Global expression patterns of R-genes in tomato and potato - von Dahlen, Janina K.; Schulz, Kerstin; Nicolai, Jessica; Rose, Laura E. (Frontiers in Plant Science, 2023)
Introduction As key-players of plant immunity, the proteins encoded by resistance genes (R-genes) recognize pathogens and initiate pathogen-specific defense responses. The expression of some R-genes carry fitness costs and therefore inducible immune responses are likely advantageous. To what degree inducible resistance driven by R-genes is triggered by pathogen infection is currently an open question. Methods In this study we analyzed the expression of 940 R-genes of tomato and potato across 315 transcriptome libraries to investigate how interspecific interactions with microbes influence R-gene expression in plants. Results We found that most R-genes are expressed at a low level. A small subset of R-genes had moderate to high levels of expression and were expressed across many independent libraries, irrespective of infection status. These R-genes include members of the class of genes called NRCs (NLR required for cell death). Approximately 10% of all R-genes were differentially expressed during infection and this included both up- and down-regulation. One factor associated with the large differences in R-gene expression was host tissue, reflecting a considerable degree of tissue-specific transcriptional regulation of this class of genes. Discussion These results call into question the widespread view that R-gene expression is induced upon pathogen attack. Instead, a small core set of R-genes is constitutively expressed, imparting upon the plant a ready-to-detect and defend status.